Clinical management of drug resistant tuberculosis: A comprehensive review - Jain, Sonal; Kumar, Arun (Asian Journal of Medical Sciences, 2014)
Despite the introduction 40 years ago of the inexpensive and effective four-drug (isoniazid, rifampicin, pyrazinamide and ethambutol) treatment regimen, tuberculosis (TB) continues to cause considerable morbidity and mortality worldwide. This is because of development of drug resistance in tuberculosis strains, usually called as MDR/XDR-TB. Consequently, novel drugs and regimens for management of these drug resistant TB forms are emerging. Such regimens probably utilize both repurposed drugs and new chemical drugs. This article covers current concepts and recent advances in TB drug discovery and development. An updated review of the mechanisms of action and resistance of the main old and new anti-tuberculosis agents has been described. The consensus statements from RNTCP for management of MDR/XDR-TB have also been discussed. Asian Journal of Medical Science, Volume-5(3) 2014: 1-9 DOI: http://dx.doi.org/10.3126/ajms.v5i3.9698